2013
DOI: 10.1136/injuryprev-2013-041023
|View full text |Cite
|
Sign up to set email alerts
|

Bus stops and pedestrian–motor vehicle collisions in Lima, Peru: a matched case–control study

Abstract: Objective To evaluate the relationship between bus stop characteristics and pedestrian-motor vehicle collisions. Design Matched case-control study where the units of study were pedestrian crossing. Setting Random sample of 11 police commissaries in Lima, Peru. Data collection occurred from February, 2011 to September, 2011. Participants 97 intersection cases representing 1,134 collisions and 40 mid-block cases representing 469 collisions that occurred between October, 2010 and January, 2011 and their mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…The results showed that the crash risk was approximately eight times greater per crossing violation event than that of a legal crossing. Quistberg et al (2015) examined the relationship between bus stops and pedestrians' crashes in urban Lima, Peru. The study reported that the presence of a bus stop in an intersection was threefold more likely to result in a pedestrian crash.…”
Section: Pedestrian and Road Side Activitiesmentioning
confidence: 99%
“…The results showed that the crash risk was approximately eight times greater per crossing violation event than that of a legal crossing. Quistberg et al (2015) examined the relationship between bus stops and pedestrians' crashes in urban Lima, Peru. The study reported that the presence of a bus stop in an intersection was threefold more likely to result in a pedestrian crash.…”
Section: Pedestrian and Road Side Activitiesmentioning
confidence: 99%
“…Las paradas de autobuses no se usan de forma segura al salir y entrar al tráfico, tal como detallan los planificadores de la ciudad. El aumento del riesgo para los peatones es una consecuencia involuntaria de las áreas destinadas a los autobuses, cuando existen fuertes incentivos económicos para recoger pasajeros siempre que sea posible, con una aplicación limitada de la ley (Quistberg et al, 2015).…”
Section: 2unclassified
“…Engineers and policy makers may consider improving the coordination of the various types of traffic control signals, consistency of construction, safe traffic speeds, and caution signage and barriers around at-grade rail at or around intersections in downtown for safety improvement. Shifting bus stops away from intersection near-side corners to far-side or mid-block locations would likely reduce risks as well (Quistberg et al 2015;Retting et al 2003).…”
Section: Tl Intersectionsmentioning
confidence: 99%